Risk of age-related macular degeneration according to the chronic kidney disease and proteinuria in Korea: a 10-year nationwide cohort study - Junhee Park; Kyungdo Han; Bongseong Kim; Kyungho Lee; Hye Ryoun Jang; Je Moon Yoon; Dong Hui Lim; Dong Wook Shin (Scientific Reports)
Abstract The association between chronic kidney disease (CKD) and the risk of age-related macular degeneration (AMD) is unclear. Our study aimed to evaluate this relationship considering the potential impact of proteinuria. This retrospective cohort study used a large representative population sample from the Korean National Health Insurance Service database (2009–2019) of individuals who participated in a national health screening program in 2009. CKD was determined by estimated glomerular filtration rate (eGFR). Proteinuria was assessed using dipstick urinalysis. AMD was identified according to International Classification Disease, Tenth Revision, codes in claims data. The Cox regression hazards model was used to estimate the association between CKD and risk of AMD. Among 4,005,946 participants, 400,189 (10.0%) had CKD. There was no significant association between CKD and AMD, but a positive relationship was identified between proteinuria and AMD. In stratification analysis with age and sex, the risk of AMD was more evident in younger (< 65 years) than older individuals (P-interaction < 0.001) and in men than women (P-interaction < 0.001). A positive association between proteinuria and AMD risk was observed and was prominent in younger males.